2011
DOI: 10.1007/s12253-011-9438-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Plasma Circulating DNA Using Quantitative PCR for the Detection of Hepatocellular Carcinoma

Abstract: Circulating DNA is a potential biomarker for tumor diagnosis and prognosis. This study was aimed to quantify the circulating DNA in plasma from patients with hepatocellular carcinoma (HCC) using quantitative PCR and evaluate its potential clinical value. Blood samples were collected from 72 patients with HCC, 37 with liver cirrhosis or chronic hepatitis and 41 healthy volunteers. Plasma DNA was extracted and quantified by a real-time quantitative PCR method. The diagnostic and prognostic value of plasma DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 21 publications
2
72
0
1
Order By: Relevance
“…Moreover, plasma DNA and serum AFP revealed an elevated AUC of 0.974 with 95.1% sensitivity and 94.4% specificity in discriminating HCC from normal controls. Furthermore, the plasma DNA levels were positively associated with tumor size and vascular invasion (P = 0.012 and P = 0.035 respectively) [77] . However further studies are needed due to the controversial results related to the methodology used.…”
Section: Cell-free Tumor Associated Dnamentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, plasma DNA and serum AFP revealed an elevated AUC of 0.974 with 95.1% sensitivity and 94.4% specificity in discriminating HCC from normal controls. Furthermore, the plasma DNA levels were positively associated with tumor size and vascular invasion (P = 0.012 and P = 0.035 respectively) [77] . However further studies are needed due to the controversial results related to the methodology used.…”
Section: Cell-free Tumor Associated Dnamentioning
confidence: 95%
“…Recently, several studies have demonstrated that ctDNA could be a non-invasive potential biomarker [54,75] . ctDNA is highly specific and could be detected easier compared to CTCs purification, thus it could be an ideal source for the early diagnosis or as recurrence biomarker [76,77] .…”
Section: Cell-free Tumor Associated Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…progression vs. non-progression) with an almost 80 % sensitivity [148]. When plasma cfmiRNA was profiled from 12 multiple myeloma patients and eight healthy controls using TaqMan low density arrays (TLDAs) in a different set of patients, it was found that high levels of cfmiR-20a and cfmiR-148a were related to shorter relapse-free survival [149]. All these data show some promise but they need to be confirmed in studies including higher patient numbers and longer follow-up times.…”
Section: Cfmirna Quantification For Prognosis Diagnosis Follow-up Amentioning
confidence: 99%